Building Interest in Reading Through the ABC Lima Dasar Game - Pertiwi, Dian; Agustini, Ninis; Rodiah, Saleha (Edulib, 2021)
This research is conducted because of the low reading interest of Cikeruh I Public Elementary School students. The students spent more time playing than reading during their spare time. This research aims to build reading interest through "ABC Lima Dasar modifikasi" Games at Cikeruh State Elementary School I. The scope of this research is based on the traditional game modification strategy of learning, including modification of tools, improvement of game rules, change of learning approaches, and development of variations in skills. The research method used is action research. Data collection techniques to determine user needs are done by interview, observation, and literature study. While data collection techniques to assess user responses are done using a questionnaire. The results of the study showed that “ABC Lima Dasar modifikasi” Game in building up reading interest was under the needs and expectations of the school and was following the traditional learning game modification strategy by paying attention to four methods, including tool modification game rule modification, modification of learning approaches and development of skill variations. User responses after an action research study produced the fact that there was an increased interest in reading and library visits. The conclusion of this research is based on the traditional game modification strategy of learning to make students comfortable in playing, train students' skills, and make students interested in reading books in the library.